Strategi Bersaing Retail Indomaret Di Era Pasar Digital - Iswanto, Dedy (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
The purpose of this research is to find out the competitive strategy of Indomaret retail in the digital market era in order to be able to excel with mini market competitors. Liquidity and the inhibiting factors of Indomaret mini market in beating competitors in today's digital marketing era. This research method is qualitative method. This type of research is descriptive research using secondary data. Data collection techniques used in the form of study documentation, interviews and observations. Data analysis techniques used are Data Reduction, Data Presentation, and Verification.The results of this study indicate that the strategy used by the Indomaret mini market in competing in the digital era is to use a marketing strategy that includes several ways including: Creating an online store with the name Klik Indomaret, i-saku strategy, increasing RTE (ready to eat) products and Point Coffee Points. Constraints faced by Indomaret